Growth morphologies and plausible stressors ruling the formation of Late Pleistocene lacustrine carbonate buildups in the Maquinchao Basin (Argentina) - Eymard, Inès (2019)
In a seminal paper regarding the mechanisms of carbonate stromatolite formation, Ginsburg (1991, Controversies in Modern Geology, pp. 25-36) emphasized the need to question to the relative role of microbes versus environment in their formation. The Maquinchao Basin is a continental lacustrine system in southern Argentina. It provides an ideal site to study carbonate buildups, the role of microbes and environmental stressors in their development and their implications in palaeoenvironmental reconstructions. Presently the basin encompasses two lakes (Carri Laufquen Grande and Carri Laufquen Chica) joined by the ephemeral Maquinchao River. Fossil microbialites are found south and southwest of the largest lake. Preferential areas of development for fossil microbialites have been mapped using a high‐resolution differential Global Positioning System. Outcrops are located between 820 m and 830 m elevation, higher than actual lake levels and the Maquinchao River where living microbialites have been observed. Field data along with microscopical observations and X‐ray Diffraction (XRD) analyses have revealed a heterogeneity in both distribution and macro‐morphotypes since carbonate buildups display different morphologies such as crust, columns, open flower‐like, rounded and ellipsoids. Conversely, on the meso and micro‐scale they show more homogenous morphologies including laminations and shrubs. These microbial buildups are associated with basaltic substrates of variable size from pebbles to boulder. The homogeneity in meso and micro‐structures argue in favour of stable intrinsic parameters (i.e. microbial communities) whereas the variable macro‐morphotypes indicate changing extrinsic constraints such as steepness, energy and turbidity. The occurrence of distinctive morphotypes in buildups separated by outcrop and topography suggest that the Maquinchao microbialites are indicative of former larger lake. Thus, the Maquinchao microbial buildups are a valuable proxy for water‐level evolution and therefore palaeoenvironmental reconstructions. They can be further used to interpret the apparently random distribution of morphological types and extension of microbialites in the geological past.